The Royal Exchange Assurance : a history of British insurance 1720-1970 - Supple, Barry (Cambridge, England : University Press, 1970)
History of the development of British history insurance;the Royal Exchange Assurance story.
Includes index.
Includes bibliographical references: p. 550-564.
obn 25/01/2019
Loans
Keywords: Insurance